Augmented Reality Empowered Responsible Tourism: Leveraging Social Media Applications for Generation Z Tourists in the Yogyakarta - Ramadhan, Shofyan Hadi (Politeknik Negeri Bali, 2024)
This research delves into the integration of augmented reality (AR) technology through Instagram filters to enhance responsible tourism practices. With a specific focus on Generation Z tourists in the Yogyakarta Special District, we recognize the importance of collective action in shaping the future of tourism. Despite the government's continuous efforts, responsible tourism implementation faces challenges, leading to cultural and environmental issues due to the increasing number of tourists. Leveraging the preferences and influence of Generation Z, this study proposes the application of AR through Instagram filters as a solution to engage and educate tourists on responsible tourism principles. The methodology involves the construction of AR system models and Instagram filter user interfaces, followed by observation and interviews with Generation Z users. The results indicate that AR filters can effectively convey information about cultural and historical assets, facilitate digital map navigation, and encourage Generation Z tourists to actively contribute to responsible tourism practices. This research underscores the significance of embracing innovative technologies to foster responsible tourism in the Yogyakarta Special District and emphasizes the collaborative nature of this endeavor, requiring the active participation of the government, tourists, and digital artists for sustainable tourism development.